SURVEI KEMAMPUAN PASSING BAWAH BOLA VOLI SISWA KELAS VI SD NEGERI 201 DESA TELAGO LIMO KECAMATAN BERBAK - Antonius Sirimetuk; Roli Mardian; Iwan Budi Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the level of underhand passing skills of sixth-grade students at SD Negeri 201 Desa Telago Limo, Berbak District. The background of this study stems from the fact that volleyball lessons in primary schools still face limitations in terms of time and facilities, resulting in students' mastery of basic techniques not being optimal. The underhand passing technique is a very important basic skill in volleyball because it serves to control the ball and initiate attack patterns. The research method used was a survey method with a lower passing ability test technique based on the Ministry of Education and Culture instrument (1999:7–14), which assessed three aspects, namely initial posture, execution, and final posture. The research subjects consisted of 20 sixth-grade students at SD Negeri 201 Telago Limo Village, Berbak District. The data were analysed using frequency and percentage calculations to determine the students' ability categories. The results of the study indicate that three students (15%) had good underhand passing skills, 15 students (75%) had moderate skills, and two students (10%) had poor skills. Thus, it can be concluded that the underhand passing skills of sixth-grade students at SD Negeri 201 Desa Telago Limo, Berbak Subdistrict, were generally moderate. The results of this study are expected to provide input for physical education teachers to improve learning strategies and add variety to exercises so that students' basic volleyball skills can develop more optimally.